Population Abundance and Frequency of Visits Forcipomyia spp. (Diptera: Ceratopogonidae) on Cocoa Plantations in Lima Puluh Kota District, Indonesia: Kelimpahan Populasi dan Frekuensi Kunjungan Forcipomyia spp. (Diptera: Ceratopogonidae) pada Perkebunan Kakao di Kabupaten Lima Puluh Kota, Indonesia - Sri Heriza; Yulia Dewi; Aswaldi Anwar; Zahlul Ikhsan (Jurusan Budidaya Perkebunan, 2024)
Forcipomyia spp. is a pollinator insect on cacao plants that belongs to the Ceratopogonidae Family, Diptera Order. The objectives of this research were to determine the abundance of the insect population of Forcipomyia spp. in Lima Puluh Kota District and to determine the frequency of visits of those insects to cacao flowers. This research was conducted on a small smallholder plantation in Sungai Talang Village, Lima Puluh Kota District. Then, the samples obtained were identified at the Andalas University Laboratory. This research was conducted using a survey method and purposive sampling technique. Five cacao plants were selected in each plot of land, and then three flower beds per plant were selected to bloom. Sampling was carried out by installing yellow sticky traps. The insects obtained were put into a collection bottle filled with 96% alcohol to preserve those insects, and then the abundance of Forcipomyia spp. Insects were calculated. The research results showed that the highest insect abundance was in Jorong Guguak Nunang: 1.260 individuals, then in Jorong Bukik Apik: 1.061 individuals and the lowest was in Jorong Boncah: 1.045 individuals. The highest frequency of visits was in the morning, with an average of 648 individuals/60 minutes. The insect diversity index based on the Shannon-Wienner Diversity Index in Jorong Guguak Nunang was 1,97; in Jorong Boncah, it was 2,21; in Jorong Bukik Apik was 1,88, and all of it is in the medium diversity level category.